Bone mineral density and fracture risk with long-term use of inhaled corticosteroids in patients with asthma: systematic review and meta-analysis. Issue 11 (24th November 2015) - Loke, Yoon K; Gilbert, Daniel; Thavarajah, Menaka; Blanco, Patricia; Wilson, Andrew M
Abstract : Objectives: We aimed to assess the association between long-term use of inhaled corticosteroids (ICS) and bone adverse effects in patients with asthma. Design: Systematic review and meta-analysis of fracture risk and changes in bone mineral density with long-term ICS use in asthma. Methods: We initially searched MEDLINE and EMBASE in July 2013, and performed an updated PubMed search in December 2014. We selected randomised controlled trials (RCTs) and controlled observational studies of any ICS (duration at least 12 months) compared to non-ICS use in patients with asthma. We conducted meta-analysis of ORs for fractures, and mean differences in bone mineral density. Heterogeneity was assessed using the I 2 statistic. Results: We included 18 studies (7 RCTs and 11 observational studies) in the systematic review. Meta-analysis of observational studies did not demonstrate any significant association between ICS and fractures in children (pooled OR 1.02, 95% CI 0.94 to 1.10, two studies), or adults (pooled OR 1.09, 95% CI 0.45 to 2.62, four studies). Three RCTs and three observational studies in children reported on bone mineral density at the lumbar spine, and our meta-analysis did not show significant reductions with ICS use. Three RCTs and four observational studies in adults reported on ICS use and bone mineral density at the lumbar spine and femur, with no significant reductions found in the meta-analysis compared to control. Conclusions: ICS use for ≥12 months in adults or children with asthma was not significantly associated with harmful effects on fractures or bone mineral density.